Prescriptions of newer glucose regulating agents in older hospitalized patients with type 2 diabetes A retrospective cohort study - Drs. Merel L.J.M. Janssen; Dr. Carolien M.J. van der Linden; Dr. Maarten J. Deenen; Dr. Petra E. Spies; Drs. Anne Jacobs (Diabetes Epidemiology and Management, 2023)
Aims: GLP-1-analogues, DPP4-inhibitors, and SGLT2-inhibitors have become available to treat type 2 diabetes. The extent to which these glucose regulating agents (GRA) are prescribed to older patients is unknown. Methods: We performed a retrospective observational cohort study including all clinical admissions of patients with one or more prescriptions for non-insulin GRA between 2017 and 2021. We analyzed prescription trends and differences in prescription prevalences for frail and non-frail older patients, as well as older (≥ 70 years) versus younger patients. Results: In total 11.5% of admissions had one prescription or more of newer GRA; GLP-1-analogues 1.6%, DPP4-inhibitors 7.3% and SGLT2-inhibitors 2.3%. Total prescription prevalence increased from 8.4% to 16.3% (p < 0.001). Prescription prevalence was 11.1% (N = 129) in admissions of frail patients versus 14.6% (N = 344) of non-frail patients (p = 0.005) and 15.0% in admissions of younger patients versus 11.5% of older patients (p < 0.001). Conclusions: Prescription prevalence of newer GRA in clinical admissions of older patients (≥ 70 years) increased from 2017 to 2021. Prevalence was lower in admissions of frail and older patients, possibly because they are undertreated due to a lack of clear recommendations for older patients in guidelines and underrepresentation in clinical trials.